Comparison of kinetic and enzymatic properties of intracellular phosphoserine aminotransferases from alkaliphilic and neutralophilic bacteria - Marianne Koivulehto; Natalia Battchikova; Saara Korpela; Elvira Khalikova; Anton Zavialov; Timo Korpela (DE GRUYTER POLAND SP Z O O, 2025)
Intracellular pyridoxal 5'-phosphate (PLP) -dependent recombinant phosphoserine aminotransferases (PSATs; EC 2.6.1.52) from two alkaliphilic Bacillus strains were overproduced in Escherichia coli, purified to homogeneity and their enzymological characteristics were compared to PSAT from neutralophilic E. coll. Some of the enzymatic characteristics of the PSATs from the alkaliphiles were unique, showing high and sharp pl I optimal of the activity related to putative internal pH inside the microbes. The specific activities of all of the studied enzymes were similar (42-44 U/mg) as measured at the pH optima of the enzymes. The spectrophotometric acid-base titration of the PLP chromophore of the enzymes from the alkaliphiles showed that the pH optimum of the activity appeared at the pH wherein the active sites were half-protonated. Detachment of PLP from holoenzymes did not take place even at pH up to 11. The kinetics of the activity loss at acid and alkaline pHs were similar in all three enzymes and followed similar kinetics. The available 3-D structural data is discussed as well as the role of protons at the active site of aminotransferases.